Republic of Mozambique : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
In this paper, the following statistical data are presented in detail: gross domestic product, savings and investment, production of major marketed crops, marketed livestock, industrial production by sector, prices of petroleum products, transport and communication activity, import prices of oil products, government finances and revenue, monetary survey, interest rates, balance of payments, foreign trade indicators, expenditure on the social sector, commodity composition of exports, exchange rates, exports by country of destination, imports by country of origin, and budget subsidies to enterprises.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet